Planning of Strategic Scenarios in the Public University of Peru - Narciso Gómez, Kennedy (2019)
The Planning of strategic scenarios in the Public University in Peru through the prospective methodology and the competences of the human resources allows to enhance the academic and administrative management of the university. The formulation, implementation and control of the model requires effective leadership of the Rector and the Members of the University Council. In these times it is to set aside the fight for private interests, but to focus on the welfare of students, teachers and non-teachers and to expand the actions of the University to other national and international levels. The strategic scenario planning model develops the following activities: The strategic decision; identification of important decision factors (FIDE); identification of the driving forces of the environment (FIE); impact and uncertainty matrix; selection of scenarios; comparative table of scenarios; threats and opportunities by scenarios.